Utilization of Laser Turbidimeter to Measure the Concentration of Starch Suspension as a Model for Measurement of Sperm Turbidity - Eryzki Triardianto; Mas Mansyur (Rifa'Institute, 2022)
Introduction: Turbidimeter is a tool that serves to determine or measure the level of turbidity of water. Based on the similarity in composition between starch and sperm fluid composition, such as protein, carbohydrates, fat, iron, starch suspension was chosen as a model for measuring sperm turbidity. By using a laser turbidimeter to measure the concentration of starch suspension, it is hoped that it will provide an alternative model that is appropriate for measuring sperm turbidity in the future. Methods: The data were processed using pearson correlation analysis by looking for the relationship between starch concentration and laser light intensity. Then performed linear regression analysis by looking for the equation of the regression line. Objective: This study aims to see the effectiveness of the laser Turbidimeter to measure the level of turbidity of sperm Results: The highest laser intensity value is at a starch concentration of 20%, with an intensity value of 0.071. While the lowest laser intensity value is at a starch concentration of 80%, with an intensity value of 0.032. The cloudier the starch, the harder it is for the laser light to penetrate it, resulting in a lower intensity value. The results also show that the results of the pearson correlation statistic test are -0.901 and with a significance value of 0.006, or it can be interpreted as less than 0.05. Conclusion: With these results it can be explained that there is a relationship between starch concentration and laser light intensity. However, this study also has many shortcomings in terms of research and analysis methods. We hope that there will be further research that can be better in terms of research methods and analysis so as to produce better results